The Application of “The Jungle Book” Theme in the Interior Design of Manimonki Animation Studio in Surakarta - Akbar, Muhammad Fakhrezi; Studyanto , Anung B. (Institut Seni Indonesia Surakarta, 2023)
Indonesia is one of the countries with the highest popularity of animation in the world. However, the city of Surakarta lacks facilities to develop and support the potential of animation film-making communities. The lack of attention from the local government as a facilitator and enabler poses a problem, leading these communities to prefer working in larger cities with national-scale studios, thereby risking Surakarta's market segment in animation. This study aims to design the interior of Manimonki Animation Studio in Surakarta to provide a facility that can accommodate and support the local animation film-making community, enhancing the growth of the animation industry in Indonesia to compete internationally. The interior design of this studio adopts a unique theme,